(untitled) (Research, Society and Development, 2020)
Part of the data on this work relies on a doctoral research. The study aimed to problematize about Science Teaching in a Waldorf school, Montessori school and Escola da Ponte, having as guiding aspects the organization of spaces, knowledge and evaluation methods of each analyzed school. As a theoretical reference, we adopted the assumptions of differentiated pedagogy and simultaneously, the field of the curriculum. Methodologically, the article points as sources of research to three directions: a theoretical and systematic review in the light of the fields of science teaching and the field of the curriculum; documentary research around the websites of schools that are pedagogically oriented from the pedagogies under discussion; and finally, field journal data based on differentiated pedagogy observations in three schools. The results showed other ways of organizing spaces, different ways of evaluating and approaching school content, more specifically in the scope of Science Teaching. Finally, the work allows a reflection and awareness about the traditional teaching that still constitutes in the great majority in schools.